Trends in Helicobacter pylori-related gastric ulcer research from 2012 to 2022: A bibliometric and visual analysis - Yu, Chang; Qiu, Jingyue; Xiong, Meng; Ou, Chen; Zeng, Meiyan; Song, Houpan (Frontiers in Medicine, 2022)
Background Helicobacter pylori-related gastric ulcer (H. pylori-related GU) is one of the most common digestive system diseases that have received widespread attention from researchers. The purpose of this article was to analyze the research status and hotspots of H. pylori-related GU and to predict its future research directions. Methods The article and review papers associated with H. pylori-related GU published from 2012 to 2022 were retrieved from the Web of Science Core Collection (WoSCC). The analysis of knowledge maps and bibliometrics was done with CiteSpace 6.1.R2 Basic and VOSviewer 1.6.18. Results A total of 2,971 articles were included in the study. Between 2012 and 2022, the number of papers published showed an increasing trend. China was the most prolific country, and the United States was the most influential country. Baylor College of Medicine had the largest number of publications and citations among publishing agencies. World Journal of Gastroenterology published the most articles on the H. pylori-related GU field, and GUT was the journal with the most cited articles. Yamaoka Y from Japan was the most productive author, and Graham DY from the USA was the most influential author. A keyword and reference analysis showed that the hot topics of research were the mechanism of H. pylori and the treatment of H. pylori-related GU. The keywords that emerged in the recent 5 years were oxidative stress, probiotics, competitive acid blocker, vonoprazan, gut microbiota, and neutrophil-activating protein. Conclusion Over the recent 10 years, research on H. pylori-related GU has generally shown an increasing trend. The treatment and pathogenesis of H. pylori-related GU remain a hot topic of research. The treatment of H. pylori by oxidative stress and competitive acid inhibitor mechanisms, the influence of gastrointestinal flora on H. pylori, probiotic adjuvant therapy of H. pylori-related GU, and the immunoprotective effect of neutrophil activator protein could be popular research directions and trends in the future.